2005
DOI: 10.1038/sj.npp.1300830
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Amygdala-Dependent Learning by Brain-Derived Neurotrophic Factor is Mediated by Extracellular Signal-Regulated Kinase and Phosphatidylinositol-3-Kinase

Abstract: This study is designed to characterize the signal cascades by which brain-derived neurotrophic factor (BDNF) modulates long-term memory of fear conditioning. Enzyme-linked immunosorbent assay (ELISA) and Western blot analysis of tissue homogenates taken from fear-conditioned rats showed an increase in the amygdala of BDNF protein levels and its receptor TrkB phosphorylation. Bilateral administration of a TrkB ligand scavenger TrkB IgG and a Trk-specific tyrosine kinase inhibitor K252a to the amygdala impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 42 publications
8
100
0
Order By: Relevance
“…For example, fear conditioning selectively increases BDNF mRNA in the amygdala, whereas mRNAs of other neurotrophins and trophic factors are unaffected (40). BDNF protein levels and TrkB phosphorylation are also enhanced by fear conditioning (41,42). In our studies, the concentrations of BDNF protein are reduced in the PC7 KO hippocampus and amygdala.…”
Section: Discussionsupporting
confidence: 49%
“…For example, fear conditioning selectively increases BDNF mRNA in the amygdala, whereas mRNAs of other neurotrophins and trophic factors are unaffected (40). BDNF protein levels and TrkB phosphorylation are also enhanced by fear conditioning (41,42). In our studies, the concentrations of BDNF protein are reduced in the PC7 KO hippocampus and amygdala.…”
Section: Discussionsupporting
confidence: 49%
“…PI 3-kinase can directly activate MEK through protein phosphorylation Bondeva et al, 1998), or PDK-1 can directly bind and activate MEK (Sato et al, 2004). In fact, recently Ou and Gean (2006) showed that PI 3-kinase inhibitors attenuate BDNF-induced ERK phosphorylation in rat amygdala, indicating that PI 3-kinase is an upstream regulator of MAP kinase activation. Recently, we observed altered ERK-1/2 signaling at multiple levels, including alterations in activation and expression of ERK-1/2 and B-Raf in postmortem brain of suicide subjects (Dwivedi et al, 2001(Dwivedi et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…The downstream influences of IRS2 can manifest via activation of the phosphoinositide 3-kinase/protein kinase B (PI3K/AKT) pathway (44). AKT signaling affects synaptic plasticity, axonal development, amygdala-dependent learning, and behavioral responses to stress (45,46). Additionally, ISLR2 sits on the cell membrane, aids in the guiding of axons, and can facilitate the activation of trk receptors, including NTRK3 (47,48).…”
Section: Resultsmentioning
confidence: 99%